Volume 4: Advanced Manufacturing Processes; Biomedical Engineering; Multiscale Mechanics of Biological Tissues; Sciences, Engin 2012
DOI: 10.1115/esda2012-82334
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Algorithm for Digitized Rotational Parts

Abstract: It is a well known fact that Reverse Engineering techniques involve the following steps: scanning the object, pre-processing a cloud of points, processing the cloud of points, redesigning, and manufacturing the part. Difficulties arise when processing clouds of points resulted from digitization, obtaining geometrical parameters of the scanned object itself and getting the final associated CAD model. This paper presents an algorithm for the recognition of a rotational part form. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…After a complete scan of the both sides for a part, outer and inner, the two files containing the clouds of points have to be unified together to form the virtual image of the part. This step was done into a specialized software, Geomagic Studio, using a dedicated algorithm [9], designed for recognizing digitized rotational parts. The matching of the two clouds of points for a certain part considered also the fact that along the flange, the thickness does not modify and it remains at the initial value, t 0 .…”
Section: Description Of the Methods For Digital Measurementmentioning
confidence: 99%
“…After a complete scan of the both sides for a part, outer and inner, the two files containing the clouds of points have to be unified together to form the virtual image of the part. This step was done into a specialized software, Geomagic Studio, using a dedicated algorithm [9], designed for recognizing digitized rotational parts. The matching of the two clouds of points for a certain part considered also the fact that along the flange, the thickness does not modify and it remains at the initial value, t 0 .…”
Section: Description Of the Methods For Digital Measurementmentioning
confidence: 99%
“…As well, using a piece of software designed by the authors [10] the axis of the active surfaces of the tools could be found. That revealed the axes of the two tools were parallel, but not placed in the same vertical plane.…”
Section: Using 3d Scanning To Evaluate the Shape Size And Relative Po...mentioning
confidence: 99%
“…The first software system, named Rotational Primitives and Axis Recognition-RPAR, is conceived for its use in RE process of rotational parts. It has implemented a set of algorithms [5] and it is used for recognizing rotational primitives and axis for parts which contains rotational surfaces, from a cloud of points. The designer can choose, through a special interface, one of the next commands:…”
Section: Cloud Of Pointsmentioning
confidence: 99%
“…1. primitives recognising: cylinder, cone or sphere are recognized, their associated data are determined and they are exported in text files [5]; 2. axis recognising: axis position of a rotational surface is determined and two points, which belongs to it, then is exported in text file; 3. axis optimising for cutting process: the axis position of a cylinder is optimized to obtained minimum cutting depth for turning process [6]; 4. section extracting: from the cloud of points a section is extracted and exported in a text file. For example, in a cylindrical surface case, the data which are determined by the system are: the axis position and the geometrical parameters (diameters and length).…”
Section: Cloud Of Pointsmentioning
confidence: 99%